“THE RELATIONSHIP BETWEEN STUDENT’S SELF-ESTEEM AND STUDENT’S SPEAKING ABILITY OF THE TENTH GRADE AT SMK MUHAMMADIYAH 3 GEMOLONG - Sulistiawati, Sulistiawati; Handayani, Sri (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
The present study entitled the relationship between studentâ€™s self-esteem and studentâ€™s speaking ability of the tenth grade at SMK Muhammadiyah 3 Gemolong. The aim of the study was to investigate whether there is significant relationship between studentâ€™s self-esteem and and studentâ€™s speaking ability of the tenth grade students at SMK Muhammadiyah 3 Gemolong. The data were obtained by the quantitative method in correlational design.â€â€â€The study was conducted at SMK Muhamadiyah 3 Gemolong. The population were 147 students of the tenth grade at SMK Muhammadiyah 3 Gemolong in 2019/2020 academic year. The tenth grade consisted of 6 classes. The study applied random sampling technique. The sample were 22 students. The instrument to collect the data of two variables were self-esteem questionnaire and oral test of speaking ability. The questionnaire used Coopersmithâ€™s self-esteem scale that contained of 37 valid questions and the rubric of oral test to measure speaking ability based Penny Ur. The analyzing of data used SPSS 22.â€â€â€The findings of study were the tenth grade students of SMK Muh 3 Gemolong had 50% in high self â€“ esteem with the mean score 65.86 and their speaking ability were in adequate level 36% with the mean score 68.63. The coefficient relationship (rxy) 0.943. Based on the result of the study, it could be concluded that the self-esteem had high positive relationship with the speaking ability of the tenth grade students at SMK Muhammadiyah 3 Gemolong.â€â€Keywords: self-esteem, speaking ability, correlation study